2022
DOI: 10.3390/molecules27051542
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Plants from Marajó Island, Brazilian Amazon: A Narrative Review

Abstract: Diseases caused by viruses are a global threat, resulting in serious medical and social problems for humanity. They are the main contributors to many minor and major outbreaks, epidemics, and pandemics worldwide. Over the years, medicinal plants have been used as a complementary treatment in a range of diseases. In this sense, this review addresses promising antiviral plants from Marajó island, a part of the Amazon region, which is known to present a very wide biodiversity of medicinal plants. The present revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…For example, the bark of the Cinchona officinalis L. tree found in the Amazon rainforest was used to produce the world's first antimalarial drug (BBC, 2020;Cueva-Agila et al, 2019). Some argue that further research on plant-based active principles is vital in the race to develop new antiviral drugs (Gomes et al, 2022). Herbal medicine is also increasingly sought for treating mental health issues related to stress, depression, and anxiety (Faustino et al, 2010;Shahrajabian et al, 2021).…”
Section: The Herbal Medicine Renaissance: Sustainable Livelihoods For...mentioning
confidence: 99%
“…For example, the bark of the Cinchona officinalis L. tree found in the Amazon rainforest was used to produce the world's first antimalarial drug (BBC, 2020;Cueva-Agila et al, 2019). Some argue that further research on plant-based active principles is vital in the race to develop new antiviral drugs (Gomes et al, 2022). Herbal medicine is also increasingly sought for treating mental health issues related to stress, depression, and anxiety (Faustino et al, 2010;Shahrajabian et al, 2021).…”
Section: The Herbal Medicine Renaissance: Sustainable Livelihoods For...mentioning
confidence: 99%
“…The plant has also been introduced to Brazil, where it has since naturalized [ 3 ]. Therefore, A. zerumbet is currently found in the subtropical and tropical areas of South America, Oceania and Asia [ 4 ] and is variously known as Vindicá (Amazon) [ 5 ], Colônia (Brazil) [ 6 ], Yàn Shān jiāng (China) [ 7 ], yellow ginger (Fiji) [ 8 ], Chatiun in Hindi (India) [ 9 ], Punnag-champa in Bengal (India) [ 10 ], Gettō (Japan) [ 11 ], Sannin (Okinawa, Japan) [ 11 ], Atoumo (Martinique, French West Indies) [ 12 ], Yuetao (Taiwan) [ 1 ], and Riềng đẹp (Vietnam) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infusions, decoctions, and teas made from A. zerumbet leaves have been consumed as anti-hypertensives and diuretics [ 15 , 16 , 17 ]. Especially in Marajó (Brazil), the leaves have been used as remedies for colds and influenza and are added to tea and bathwater [ 5 ]. According to traditional Chinese folklore, the rhizomes of A. zerumbet can effectively treat trauma and peptic ulcers [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of influenza virus mutations capable of bypassing the action of these drugs has led to the need to continue the search for new compounds that can suppress the reproduction of the virus. One of the directions of such research is the search for pharmacologically active compounds isolated from plants. Among the various classes of antiviral compounds of plant origin, the chemically diverse group of flavonoids is a prime target for research and individual flavonoid compounds have been assessed for the safety of regular intake and antiviral activity in vitro and in vivo. It has been shown that a number of flavonoid aglycones have a pronounced ability to suppress the reproduction of various viruses in vitro and in vivo experiments, affecting various stages of their replication. One such aglycone is isorhamnetin, which occurs in plants in various glycosylated forms. Since glycosylation increases solubility, it is able to increase antiviral properties.…”
Section: Introductionmentioning
confidence: 99%